2021
DOI: 10.4308/hjb.28.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi from Four Indonesian Medicinal Plants and Their Inhibitory Effect on Plant Pathogenic Fusarium oxysporum

Abstract: The medicinal plants Centella asiatica, Curcuma xanthorrhiza, Guazuma ulmifolia, and Hydrocotyle verticillata are widely used  in Indonesian traditional medicine, but little is known about their associated endophytic fungi. This research aimed to study the diversity of endophytic fungi derived from functional parts of these plants and to evaluate their potential as antifungal agents against the plant pathogenic fungus Fusarium oxysporum. A total of 17 isolates of endophytic fungi were obtained: nine from leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…A higher extract concentration improved radial growth inhibition rates than the lowest concentration. According to Sukarno et al (2021), there were three groups of inhibition in F. oxysporum, low inhibition (<30%), moderate inhibition (30-59%), and high inhibition (>60%), which confirmed that the inhibition of W3.15 strain extract was high. The previous report showed an impressive inhibition rate against three kinds of tuber dry rot pathogens, F. acuminatum, F. equisetai, and F. tricintum, by ethyl acetate extract of Halobacillus trueperi S61 (Shen et al 2022).…”
mentioning
confidence: 70%
“…A higher extract concentration improved radial growth inhibition rates than the lowest concentration. According to Sukarno et al (2021), there were three groups of inhibition in F. oxysporum, low inhibition (<30%), moderate inhibition (30-59%), and high inhibition (>60%), which confirmed that the inhibition of W3.15 strain extract was high. The previous report showed an impressive inhibition rate against three kinds of tuber dry rot pathogens, F. acuminatum, F. equisetai, and F. tricintum, by ethyl acetate extract of Halobacillus trueperi S61 (Shen et al 2022).…”
mentioning
confidence: 70%
“…The fungus has been isolated from rhizomes of turmeric (Curcuma longa Linn.) (Septiana et al 2017), roots of ginger (Zingiber officinale Roscoe) (Ginting et al 2013), leaves of Asiatic pennywort (Centella asiatica L.) (Sukarno et al 2021) and roots of the orchid P. tankervilleae (Sufaati et al 2016). However, the phylogenetic entities of these Indonesian FSSC isolates, particularly those isolated from tropical orchids, have yet to be described.…”
Section: Discussionmentioning
confidence: 99%